MSME Marketing Trends in the 4.0 Era: Evidence from Indonesia - M. Indre Wanof; Abdul Gani (CV. Media Digital Publikasi Indonesia, 2023)
MSMEs that have carried out the production process automatically produce their business products or services. However, not a few are still confused about how to market the product. This research aims to examine what are the components of promotional media and marketing trends in the era of the industrial revolution 4.0. This research includes library research, because the research was conducted to search, analyze, make interpretations and generalizations from the facts of the results of thoughts and ideas written by marketing management experts. This research is descriptive qualitative with a secondary data analysis approach. The results of this study state that entering the era of the industrial revolution 4.0 certainly requires knowledge, insight, and skills to carry out promotion and marketing with online media for the business to be run. Online promotional media is a medium that can be used to promote or advertise with digital technology media and the internet. Social media and marketplaces are online media that can be used for promotion or at the same time used as a means to conduct online business. The results of this study are expected to be positive input for MSME actors to decide to venture into adopting social media and e-commerce.